Clinic Pharmacokinetic Profiles of Huperzine A Following Transdermal Administration to Healthy Human Volunteers - Wu, Ting; Li, Chang-Yin; Chen, Min; Zhang, Jun; Tan, Heng-Shan; Yang, Chen; Ju, Wen-Zheng (Chromatographia, 2011)
To support the rationale behind the development of the huperzine A patches and its pharmacological effects in clinical therapy, an LC–MS–MS method was developed and validated for determination of huperzine A in human plasma and then applied to the clinic pharmacokinetics study on transdermal patches of huperzine A. After a simple liquid–liquid extraction with ethyl acetate, analytes were separated on a C18 column with isocratic elution. The detection of analytes was performed on a tandem mass system equipped with an electrospray ionization source in positive mode using multiple-reaction monitoring. The MS–MS ion transitions monitored were m / z 243.2→210.1 for huperzine A and m / z 248.1→128.0 for tinidazole (internal standard). Method validation and sample analysis were performed according to FDA guidelines and the results met the acceptance criteria. The pharmacokinetic profiles of huperzine A following single transdermal administration of 8, 10 and 12 mg huperzine A to healthy human volunteers were depicted using the established method. The results showed that the pharmacokinetic behavior of huperzine A in vivo was present as linear dynamic characteristics with much longer T max , lower C max , and relatively constant plasma concentration. No gender difference and obvious adverse effects were observed from all three groups in our study. Our study indicated that the huperzine A transdermal patches could provide continuous drug delivery over 120 h with favorable tolerability. This may allow patients to obtain optimal plasma concentrations of drugs and to benefit from a longer duration of treatment.